Bio-optical studies on chlorophyll-a concentration in Hooghly River, India. (2021) - Premkumar, R.; Venkatachalapathy, R.; Visweswaran, S.
Abstract: The concentration of chlorophyll-a in the aquatic environment is a good indicator to understand its tropic status and also used to monitor the biogeochemical parameter. The aim of this study is to identify the spectral signature of Hooghly River, India using Satlantic hyperspectral ocean colour radiometer and developing the regional algorithm for retrieval for chlorophyll-a concentration. This approach is based on the development of an empirical band ratio algorithm. The calibrated results between the in-situ chlorophyll-a and in-situ remote sensing reflectance show a good correlation with R 2  = 0.77. In-situ and satellite validation also gives better accuracy (R 2  = 0.78&0.73) in the estimation of chlorophyll-a concentration. So the satellite-based approach provides a good correlation with in-situ data. This study was helped in monitoring and retrieval of chl-a concentration in the Hooghly River, Kolkata.